How could lay perspectives on successful aging complement scientific theory?: findings from a U.S. and a German life-span sample - Jopp, Daniela; Wozniak, Dagmara (The gerontologist, 2015)
Purpose of the Study: This article investigates lay perspectives of the concept of successful aging in young, middle-aged, and older adults from 2 cultures, t
Advance access publication 23 June 2014
Gesehen am 19.06.2020